THE IMPORTANCE OF DISTANCE EDUCATION - Turekeeva, Alfiya Jienbekovna (The journal of contemporary issues in business and government, 2021)
The article describes the introduction of new technologies in education,technical means and technologies such as teaching, testing and communication tools in distance learning, didactic programs, differential and integrated education in the world educational experience.